Identification of PRRSV nonstructural proteins and their function in host innate immunity - Yanhua, Li (Kansas State University, 2014)
Porcine reproductive and respiratory syndrome virus (PRRSV) employs multiple functions to modulate host’s innate immune response, and several viral nonstructural proteins (nsps) are major players. In this dissertation, the research was mainly focused on identification and functional dissection of ORF1a-encoded nsps. PRRSV replicase polyproteins encoded by ORF1a region are predicted to be processed into at least ten nonstructural proteins. In chapter 2, these predictions were verified by using a panel of newly established antibodies specific to ORF1a-encoded nsps. Most predicted nsps (nsp1β, nsp2, nsp4, nsp7α, nsp7β and nsp8) were identified, and observed to be co-localized with de novo-synthesized viral RNA in the perinuclear region of the cell. Among all PRRSV proteins screened, nsp1β is the strongest type I interferon antagonist. In chapter 3, mutagenesis analysis of nsp1β was performed to knock down nsp1β’s IFN antagonist function. A highly conserved motif, GKYLQRRLQ, was determined to be critical for nsp1β’s ability to suppress IFN-β and reporter gene expression. Double mutations introduced in this motif, K130A/R134A (type 1 PRRSV) or K124A/R128A (type 2 PRRSV), improved PRRSV’s ability to stimulate the expression of IFN-α, IFN-β and ISG15. In addition to its critical roles involving in modulating host innate immune response, in the studies of Chapter 4, we demonstrated that PRRSV nsp1β functions as a transactivator to induce the -2/-1 ribosomal frameshifting in nsp2, which results in expression of two novel PRRSV proteins, nsp2TF and nsp2N. The conserved motif GKYLQRRLQ is also determined to be critical for the transactivation function of nsp1β. In chapter 5, the interferon antagonist, de-Ub and de-ISGylation activity of newly identified nsp2TF and nsp2N were evaluated. In vitro and in vivo characterization of three nsp2TF-deficient recombinant viruses indicated that all mutant viruses have improved ability to stimulate the innate immune response and provide improved protection in mutant virus-vaccinated animals. In summary, this study verified the previously predicted PRRSV pp1a processing products, further evaluated the function of nsp1β and nsp2-related proteins. These data obtained here will provide basic knowledge for future development of vaccines and control measurements.
Keywords: Porcine reproductive and respiratory syndrome virus; nsp1β; type I interferon antagonist; programmed -2 ribosomal frameshifting; nsp2TF; vaccine development; Animal Diseases (0476); Molecular Biology (0307); Virology (0720)